2014
DOI: 10.1128/mcb.01401-13
|View full text |Cite
|
Sign up to set email alerts
|

Homer1 Alternative Splicing Is Regulated by Gonadotropin-Releasing Hormone and Modulates Gonadotropin Gene Expression

Abstract: Hypothalamic gonadotropin-releasing hormone (GnRH) plays a critical role in reproductive physiology by regulating folliclestimulating hormone (FSH) and luteinizing hormone (LH) gene expression in the pituitary. Analysis of gonadotrope deep-sequencing data identified a global regulation of pre-mRNA splicing by GnRH. Homer1, a gene encoding a postsynaptic density scaffolding protein, was selected for further study. Homer1 expresses a short splice form, Homer1a, and more-abundant long transcripts Homer1b/c. GnRH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Indeed, Auboeuf et al () reported that steroid hormone mediates splicing of target gene in mammalian tissue cultures. Similarly, Wang, Chikina, Pincas, and Sealfon () showed that hypothalamic gonadotropin releasing hormone (GnRH) that plays a critical role in reproduction, regulates pre‐mRNA splicing, and stress hormones control alternative splicing of potassium channels (Xie & McCobb, ). Taken together, our results indicate that hormones may play an important role in splicing pre‐mRNAs in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Auboeuf et al () reported that steroid hormone mediates splicing of target gene in mammalian tissue cultures. Similarly, Wang, Chikina, Pincas, and Sealfon () showed that hypothalamic gonadotropin releasing hormone (GnRH) that plays a critical role in reproduction, regulates pre‐mRNA splicing, and stress hormones control alternative splicing of potassium channels (Xie & McCobb, ). Taken together, our results indicate that hormones may play an important role in splicing pre‐mRNAs in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced phosphorylation of SRSF3 promotes the occurrence of splicing events mediated by carcinogenic SRSF3 and the generation of GBM tumors [40]. In addition, Wang et al found that hypothalamic gonadotropin-releasing hormone (GnRH) has normal reproductive function and can induce phosphorylation of SRSF3 in a time-dependent way [110].…”
Section: Phosphorylationmentioning
confidence: 99%
“…Ania-3 has previously been reported as an alternative isoform of Homer1 that responds like an immediate early gene (Bottai et al, 2002), and the change we detect here corresponds to the unique Ania-3 exon. Whether Ania-3 splicing is regulated by SRp20, as is the case for Homer1a (Wang et al, 2014), is a subject for future investigation. Las1l bin 15 appears to be a retained intron, but whether this is part of the canonical Las1l mRNA or part of a different isoform is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Isoform-specific gene expression changes are known to occur after fear conditioning, including upregulation of Bdnf IV , but not other Bdnf isoforms (Lubin, Roth, & Sweatt, 2008; Mizuno, Dempster, Mill, & Giese, 2012), and Homer1a , but not Homer1c (Mahan et al, 2012) in response to strong, three shock training protocols. The different Bdnf isoforms have distinct transcription start sites, while the expression of Homer1 isoforms is controlled by the splicing regulator SRp20 (Wang, Chikina, Pincas, & Sealfon, 2014), which is upregulated after learning (Antunes-Martins, Mizuno, Irvine, Lepicard, & Giese, 2007). These examples indicate that gene regulation after learning is more complex than gene-level differences and can be highly selective for particular isoforms of a gene.…”
Section: Introductionmentioning
confidence: 99%